Drivers and barriers to financial inclusion: New insights from Muslim countries - Akasumbawa, Muhammad Dedat Dingkoroci; Haryono, Slamet; Chairunnisa (Faculty of Economics, Universitas Islam Indonesia, 2024)
Purpose – This study examines the factors driving and barriers to financial inclusion in Organisation of Islamic Cooperation (OIC) countries.Methodology – This study employs panel data analysis using fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) methods. The sample consists of OIC countries from 2011 to 2021.Findings – According to the FMOLS model, remittances, bank stability, and government debt are key drivers of long-term financial inclusion, while inflation, trade openness, and economic development act as barriers. Bank competition does not significantly impact financial inclusion. In the DOLS model, remittances and bank stability remain significant drivers, with inflation and economic growth acting as barriers. However, in the long term, financial inclusion is not significantly influenced by government debt or competition.Implications – This study offers insights for financial institutions and governments. Financial institutions should improve their access to low-income groups and small businesses. Governments should promote financial inclusion and stability through sound macroeconomic policy. Policymakers can use these findings to focus on key factors for a sustainable economy.Originality – This study fills a gap by exploring the factors affecting financial inclusion in OIC countries, a less-studied topic. It also uses additional indicators to measure the financial inclusion index, leading to more comprehensive results.